2020
DOI: 10.1186/s42779-020-00050-8
|View full text |Cite
|
Sign up to set email alerts
|

Traditional foods and beverages in Eastern Tigray of Ethiopia

Abstract: Ethiopia is a multiethnic country with diverse cultural practices to prepare foods and beverages having significant contributions in socioeconomic development. Contrary, comprehensive documentation of the products, associated knowledge, and their sociocultural roles is incomplete. In this survey, thirteen typical traditional foods (two fermented and eleven non-fermented) and five traditional beverages (four fermented and one non-fermented) were listed referring the local community of East Tigray. The noted tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…For example, in the Korean culture, traditional food is normally considered as the first medicine [ 44 ]. In addition, studies conducted in South Africa [ 45 ] and Ethiopia [ 46 ] reported that food security and dietary diversification can be attained by exploiting indigenous food species. Therefore, future studies to investigate these associations are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Korean culture, traditional food is normally considered as the first medicine [ 44 ]. In addition, studies conducted in South Africa [ 45 ] and Ethiopia [ 46 ] reported that food security and dietary diversification can be attained by exploiting indigenous food species. Therefore, future studies to investigate these associations are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…To compare this with existing works on similar breads, Ethiopian injera has been the object of greater—and growing—attention by researchers, with 26 articles published in the period 2012–2016 showing “ injera ” in the title, abstract, or keywords, and 62 articles in the most recent 5-year period (2017–2021) [ 18 ]. Besides Ethiopian injera [ 19 ], studies have established the presence of similar traditional flatbreads in the broader region, including the ambasha , a fermented pancake-like bread, prepared by the Eastern Tigray people of Ethiopia and of Eritrea, both geographically proximate to Somalia [ 20 ]. Among the Eastern Tigray, non-fermented flatbreads such as torosho and its dry version birkuta have also been reported [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides Ethiopian injera [ 19 ], studies have established the presence of similar traditional flatbreads in the broader region, including the ambasha , a fermented pancake-like bread, prepared by the Eastern Tigray people of Ethiopia and of Eritrea, both geographically proximate to Somalia [ 20 ]. Among the Eastern Tigray, non-fermented flatbreads such as torosho and its dry version birkuta have also been reported [ 20 ]. All of these breads have been recently investigated with the aim of reviewing both traditional ethnic foodways and scientific studies related to their preparation [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination is often offered at Buddhist alms-giving ceremonies as a tradition, illustrating the importance of Meekiri in Sri Lankan food culture. Health benefits of such traditional foods can be passed into modern diets with proper interventions of modern food processing technologies [5], since food and health are directly related as detailed in Ayurvedic traditional methods of food habits and dietary preparations [6]. Fermented buffalo milk has been used as numerous indigenous beverages in Asia, e.g.…”
Section: Introductionmentioning
confidence: 99%